2022
DOI: 10.1111/jfb.14990
|View full text |Cite
|
Sign up to set email alerts
|

Straightforward upriver migration to spawning sites by chum salmon Oncorhynchus keta homing to coastal short rivers in the Sanriku region

Abstract: In chum salmon (Oncorhynchus keta) homed to the Sanriku region, Japan, most of the fish are matured in bays and spawn near river mouths in coastal short rivers; therefore, their upriver migration is extremely short, but their behavioural characteristics have remained unknown. Upriver migration in the Otsuchi River, a typical coastal river, was evaluated from behavioural and physiological aspects. Homing salmon tracked in Otsuchi Bay held in the inner bay for less than 1 day to more than 10 days before river en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The biological rhythms of Chum can vary depending on the timing of their arrival on the coast, potentially in uencing the timing and speed of their migration from the coast to rivers 44,45 . Studies in Japan, Alaska, and other areas have investigated changes in salmon migration patterns between coastal and river environments based on variations in biological rhythms using methods such as EMG telemetry and blood samples 46,47 . It has been reported that migration patterns vary depending on hormone levels and maturity 47,48 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The biological rhythms of Chum can vary depending on the timing of their arrival on the coast, potentially in uencing the timing and speed of their migration from the coast to rivers 44,45 . Studies in Japan, Alaska, and other areas have investigated changes in salmon migration patterns between coastal and river environments based on variations in biological rhythms using methods such as EMG telemetry and blood samples 46,47 . It has been reported that migration patterns vary depending on hormone levels and maturity 47,48 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Japan, Alaska, and other areas have investigated changes in salmon migration patterns between coastal and river environments based on variations in biological rhythms using methods such as EMG telemetry and blood samples 46,47 . It has been reported that migration patterns vary depending on hormone levels and maturity 47,48 . During the spawning migration period, salmon with immature gonads may stay in relatively warm coastal areas for an extended period to regulate the timing of spawning before slowly migrating to rivers, while well-matured Chum demonstrate a strategy of quickly moving to colder rivers as spawning approaches 47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation